Energy and exergy analysis of a desiccant cooling system integrated with thermal energy storage and photovoltaic/thermal-solar air collectors. (2nd January 2020) - Ma, Zhenjun; Ren, Haoshan; Sun, Zhongwei
Abstract : This paper presents an energy and exergy analysis of a desiccant cooling system integrated with an air-based thermal energy storage (TES) unit using phase change materials (PCMs) and a photovoltaic/thermal-solar air collector (PV/T-SAC). The PV/T-SAC was used to generate thermal energy for desiccant wheel regeneration and space heating, and the TES was used to solve the mismatch between thermal energy supply and demand. The performance of this system was evaluated using a simulation system developed using TRNSYS. The effects of several key parameters on solar thermal contribution, specific net electricity generation, and the exergy destructions of individual components and overall system were investigated. It was found that the system exergy destruction was mainly resulted by the PV/T-SAC. Both the exergy performance and energy performance of this system were significantly influenced by the length and PV factor of the PV/T-SAC used. The results obtained from this study could be potentially used to guide the optimal design of desiccant cooling systems integrated with thermal energy storage and solar energy systems.